Perioperative oncolytic virotherapy to counteract surgery-induced immunosuppression and improve outcomes in pancreatic ductal adenocarcinoma - Mansouri, Sarah; Daniel, Lauren; Amhis, Nawal; Leveille, Maxime; Boudreau, Jeanette E.; Alkayyal, Almohanad A.; Collin, Yves; Tai, Lee-Hwa (Frontiers in Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is a high fatality cancer with one of the worst prognoses in solid tumors. Most patients present with late stage, metastatic disease and are not eligible for potentially curative surgery. Despite complete resection, the majority of surgical patients will recur within the first two years following surgery. Postoperative immunosuppression has been described in different digestive cancers. While the underlying mechanism is not fully understood, there is compelling evidence to link surgery with disease progression and cancer metastasis in the postoperative period. However, the idea of surgery-induced immunosuppression as a facilitator of recurrence and metastatic spread has not been explored in the context of pancreatic cancer. By surveying the existing literature on surgical stress in mostly digestive cancers, we propose a novel practice-changing paradigm: alleviate surgery-induced immunosuppression and improve oncological outcome in PDAC surgical patients by administering oncolytic virotherapy in the perioperative period.